Post-stroke epileptic seizures: risk factors, clinical presentation, principles of diagnosis and treatment - O. A.M. Al-Sahli; L. М. Tibekina; O. P. Subbotina; V. V. Flud (Эпилепсия и пароксизмальные состояния)
Post-stroke developing epileptic seizures represent a severe complication aggravating post-stroke condition. Epilepsy can exacerbate cognitive, psychopathological, somatic disorders resulting from cerebrovascular and comorbid diseases. Despite that post-stroke epilepsy (PSE) is a rather common type of acquired structural epilepsy, the issues related to diagnosis and management often raise difficulties for clinicians. Patients with severe strokes affecting brain, cortex, acute symptomatic seizures and intracerebral hemorrhage are at greater risk of developing PSE. Timely neurophysiological, neuroradiological research methods, assessed blood biomarkers as well as prognostic models provide information that complements PSE clinical risk factors. The management of post-stroke acute and long-term (late) symptomatic seizures differs markedly. At the same time, the choice of an optimal anticonvulsant drug should be based not only on its effectiveness, but also on related side effects, pharmacodynamics as well as an impact on concomitant diseases. Drug interactions, especially between anticonvulsants and anticoagulants or antiplatelet agents also affect a choice of treatment, which should be taken into consideration for management of PSE patients.